Advances in fish and wildlife ecology and biology - Kaul, Bansi Lal 1942- (Daya Publishing House, 1999)
With reference to Jammu and Kashmir, India; contributed articles; commemoration volume for Y.R. Malhotra, Vice-chancellor, University of Jammu.